Use of Integrative and Complementary Practices in the social isolation period of COVID-19 in Brazil (Research, Society and Development, 2020)
The aim of this study was to analyze the use of Integrative and Complementary Health Practices (PICS) during the COVID-19 pandemic among residents of Brazil, associating it with sociodemographic factors and the presence of chronic diseases. This is a cross-sectional study with non-probabilistic sampling for convenience, whose information was obtained from the application of an online questionnaire, from April 2020 to September 2020. The questionnaire included information from 691 individuals, aged 18 and over, on their sociodemographic, health and use of PICS aspects during the pandemic period. The results show that the frequency of PICS use was 33.9%, with 61.9% residing in the Midwest Region, 38.6% having two or more chronic diseases, 37.6% female and 38, 9% graduate students. Meditation, Yoga and Homeopathy were the most used practices, corresponding to 65.4% of all practices mentioned in the study. It is recommended to review the strategies and carry out new studies in a broader and more detailed way of the macro-regions in order to further understand the potential of using PICS.